Role of Reverse Transcriptase Polymerase Chain Reaction in Cornea Donors During the COVID-19 Pandemic. Issue 8 (August 2021) - Arora, Ritu; Sharda, Shipra; Sahu, Jigyasa; Manchanda, Vikas; Jain, Parul; Gupta, Isha; Gotmare, Nikhil; Bharti, Nisha
Abstract : Purpose: The purpose of this study was to report the analysis of reverse transcriptase polymerase chain reaction (RT-PCR) of nasopharyngeal (NP) samples of cornea donors dying because of causes unrelated to severe acute respiratory coronavirus (SARS-CoV-2). Methods: A retrospective analysis of all cornea donors dying from causes other than SARS-CoV-2 between August 2020 and December 2020 was performed. Informed consent was obtained from the next of kin of the deceased for RT-PCR testing from NP swabs. Rapid antigen testing from all the deceased was performed before in situ cornea excision. In addition, NP samples in viral transport media for RT-PCR were also collected for SARS-CoV-2 analysis. Corneas were released from the eye bank only after a negative RT-PCR report. Result: One hundred eighteen corneas from 59 donors were obtained by the eye bank. Eleven donors (18.64%) were positive for SARS-CoV-2 on RT-PCR testing. Six of these 11 donors had a Ct value of E gene less than 25. Conclusions: NP samples of cornea donors dying due to causes other than coronavirus disease-19 were positive for SARS-CoV-2 on RT-PCR. This implicates that donors could be having asymptomatic/undetected coronavirus disease infection. We recommend adding the routine testing of NP samples of all cornea donors in the eye banking protocol in this ongoing SARS-CoV-2 pandemic.